Social Relations Reflected in the Use of Phatic Communication Viewed from Critical Classroom Discourse Analysis - Fajar, Muh Fajar; Sulistyowati, Henny (New Language Dimensions, 2022)
Studying social relations embedded in the use of phatic expression plays an important role to detect the position of each participant in the communication events. This research was aimed at investigating how the lecturers of the English Department STKIP PGRI Jombang enacted phatic communication as part of a power and solidarity strategy in maintaining good social relations through dialogues with their students. It employed qualitative research by adopting the theory of critical classroom discourse analysis to investigate how the lecturer enacted phatic communication as power and solidarity strategies to the students in the classroom. It related the examination of phatic communication and social analysis to get true data analysis of the research. The findings showed the lecturers enacted phatic communication as a powerful strategy for their students by addressing the students in terms of the learning process and controlling the preparation of the group discussion. Furthermore, the lecturers also enacted phatic communication as a solidarity strategy with their students by exercising personal experiences and expressing sad feelings to the student whose father passed away. Thus, it could be concluded that when the lecturers exercised power over the students indicated that their social relations are unequal. On the contrary, the solidarity exposed by the lecturers to their students indicated that their social relations are equal.